2022
DOI: 10.1002/yea.3815
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced flavour profiles through radicicol induced genomic variation in the lager yeasts, Saccharomyces pastorianus

Abstract: The yeasts, Saccharomyces pastorianus, are hybrids of Saccharomyces cerevisiae and Saccharomyces eubayanus and have acquired traits from the combined parental genomes such as ability to ferment a range of sugars at low temperatures and to produce aromatic flavour compounds, allowing for the production of lager beers with crisp, clean flavours. The polyploid strains are sterile and have reached an evolutionary bottleneck for genetic variation. Here we describe an accelerated evolution approach to obtain lager y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
(73 reference statements)
0
1
0
Order By: Relevance
“…A study has found that yeast could use the Harris pathway to achieve the synthesis of phenylpyruvate. Phosphoenolpyruvate (PEP) from the glycolytic pathway and erythrin 4‐phosphate (E4P) from the pentose phosphate pathway can generate phenylpyruvate through multi‐step enzyme catalysis 32 . Among them, ARO1 (encoding a penta‐functional AROM polypeptide (that include dehydroquinate synthase, dehydroquinate dehydratase, shikimate dehydrogenase, shikimate kinase and 5‐enolpyruvylshikimate‐3‐phosphate)) and CS (encoding chorismate synthase) genes are key genes for the synthesis of phenylpyruvate in the Harris upstream pathway.…”
Section: Discussionmentioning
confidence: 99%
“…A study has found that yeast could use the Harris pathway to achieve the synthesis of phenylpyruvate. Phosphoenolpyruvate (PEP) from the glycolytic pathway and erythrin 4‐phosphate (E4P) from the pentose phosphate pathway can generate phenylpyruvate through multi‐step enzyme catalysis 32 . Among them, ARO1 (encoding a penta‐functional AROM polypeptide (that include dehydroquinate synthase, dehydroquinate dehydratase, shikimate dehydrogenase, shikimate kinase and 5‐enolpyruvylshikimate‐3‐phosphate)) and CS (encoding chorismate synthase) genes are key genes for the synthesis of phenylpyruvate in the Harris upstream pathway.…”
Section: Discussionmentioning
confidence: 99%